(3GdeONd Edi Yde GdfLhes - (3YHO GdYRjR Hf YKeGf GdbHjUj GdgGTej, CHh GdUbQ,J (B380 (3g` s
(3ChdgG (B:s
(3bGd CHh GdUbQ CeG HYO aEfi deG QCjJ LeGYI ef eJbOeI UfGYI CMcGe GdfLhe bO YedhG cJHkG SehgG eOGNd Edi gPg GdUfGYI aCdaJ gPG GdcJGH s
(3BNQgG (B:s
(3hjdbi ef GdWGdY GdHjJ GdKGfi YTQ Sge GdCYOGA dgQeS jDNP HGdfgGQ hGddjd ef RMd Edi GdeQjM hjdbi ef GdWGdY agPg SgGe GdHjhJ GdEKfi YTQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdeNWhW eQJH Ydi NeSI aUhds
(3cJHJ Hbde Hg VHW heged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B252s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B399 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 - (3U (B217 s
Keywords: (3Gdadcs